E-Learning as a Solution for Arabic Writing Skills: A Website-Based Approach - Basith, Abdul (Al-Muyassar: Journal of Arabic Education, 2025)
This research aims to examine the implementation of website-based e-learning as a solution to improve Arabic writing skills among students. Good writing skills are very important for the development of communication and reasoning abilities, but many students experience difficulties in this area. Website-based e-learning has become an effective alternative because it can be accessed anytime and anywhere, providing flexibility for students to learn independently with guidance from the provided materials. This research uses a quantitative approach with an experimental method, involving two groups of students, namely the experimental group that uses a website-based e-learning platform and the control group that uses conventional learning methods. Data collection was conducted through pre-tests and post-tests to measure the improvement in students' writing skills. The research results show that the experimental group using website-based e-learning experienced a significant improvement in writing skills compared to the control group. This indicates that website-based e-learning can be an effective solution in improving writing skills, as it provides an interactive, personalized, and easily accessible learning experience. This research suggests that website-based e-learning can be more widely implemented in the context of education, especially to address the difficulties faced by students in developing Arabic writing skills.